The crystal structure of 3-bromopicolinic acid, C6H4BrNO2 - Huang Guang (Zeitschrift für Kristallographie - New Crystal Structures, 2021)
C6H4BrNO2, orthorhombic, Pna21 (no. 33), a = 14.3975(12) Å, b = 7.5773(7) Å, c = 12.2500(10) Å, β = 90°, V = 1336.4(2) Å3, Z = 8, R gt(F) = 0.0281, wR ref(F 2) = 0.0536, T = 150(2) K.